Promising practices of disability inclusion in addressing disaster displacement - Uzair, Y; Yasukawa, L; Bari, N (Refugee Studies Centre, University of Oxford, 2022)
Persons with disabilities are disproportionately affected by climate change and disaster displacement but promising examples of more inclusive planning and responses are emerging.